STABILITY-INDICATING RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE DETERMINATION OF ROSUVASTATIN (CALCIUM) IN PHARMACEUTICAL DOSAGE FORM (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
A stability indicating, accurate, specific, linear and sensitive reverse phase-HPLC method has been developed and validated for the determination of Rosuvastatin as calcium, (ROS) in pharmaceutical dosage form. The chromatographic separation was performed using end capped (Luna) C18 Column (250 mm × 4.6 mm, 5μm particle size). Mobile phase A was prepared by mixing 3.0g/l Ammonium dihydrogen phosphate in distilled water: Methanol: Acetonitrile: Tetrahydrofuran in the ratios (400:20:100:5v/v). To 1000 ml of the resulting solution 1 ml of triethylamine was added then the pH was adjusted to 6.3 with 5% v/v orthophosphoric acid. Mobile phase B was prepared by mixing Acetonitrile: Methanol: Tetrahydrofuran in the ratios (500:50:5v/v). Other chromatographic conditions such as flow rate set at 2.0 ml/min and 30°C column temperature with the detection wavelength at 243nm. The retention times of Rosuvastatin was found to be about 16 min. The linearity was performed in the concentration range of 40.0-60.0μg/ml with a squared correlation coefficient of 0.99998. The percentage purity of ROS was found to be >99.8%. The percentage recovery was determined for ROS and was found to be 100.067%. The developed analytical method has been validated for specificity, linearity, precision, accuracy, ruggedness and robustness which were within the acceptance limit according to ICH guidelines. All the degradation products obtained by stress conditions were found to be well separated from the principal peak, which means that the ROS peaks were highly pure in all chromatograms obtained. The developed method was successfully employed for routine quality control and stability analysis of ROS in pharmaceutical dosage forms.